Basic properties of the mangrove tree branches as a raw material of wood pellets and briquettes. Issue 1 (November 2021) - Nuryawan, A; Syahputra, R S; Azhar, I; Risnasari, I
Abstract: In order to sustain mangrove forests, only branches part of the mangrove trees have been utilized. In this context, these parts have been used as the raw material of wood pellets and briquettes. These solid biofuels are produced by compressing pulverized woody biomass with or without additives in cubic-form or cylindrical units. In this study, five predominant mangrove trees, namely Avicennia marina, Bruguiera sexangula, Excoecaria agallocha, Rhizopora apiculata, and R. mucronata, have been harvested their branches. Wood with and without bark derived from branches has been investigated for their fundamental properties, namely percentage of bark, ash-content, and physical properties (moisture content, density, and specific gravity). These properties will determine the quality class of the resulted wood pellets and briquettes considering pre-treatment or the nature of the branches' wood.